Rice Science: Biotechnological and Molecular Advancements - Verma, Deepak Kumar; Srivastav, Prem Prakash; Nadaf, Altafhusain B. (Apple Academic Press, 2018)
A significant crop in our global society, rice is a staple food product for over half of the world's population. New technologies are being researched and utilized for increasing the overall production of strong rice crops throughout the world. This book focuses on the new areas of research on the most recent biotechnological and molecular techniques to aid in this endeavor. The researchers who have contributed to this compendium are international leaders in their respective fields. The original research included in the volume is strengthened through the addition of surveys, reviews, success stories, and other aspects that impact the global agricultural industry